Some thoughts on the European Communities' Budget - Christopher Tugendhat (Intereconomics, 1980)
The Budget of the European Communities has recently moved from the political periphery to the centre of the stage. The European Parliament and the Council of Ministers could not agree on the 1980 Budget, the main issue being its domination by the expenditures on agriculture. Moreover, a financial crisis is to be expected for 1981 or 1982 as the Community's financial “own Resources” will no longer be sufficient. Finally there is the still unsolved problem of the unequal way in which the costs and benefits of the Community Budget are distributed among the Member States. Christopher Tugendhat, Budget Commissioner of the European Communities, comments on these questions.
Keywords: 330; European Communities